Erythropoietic and non-erythropoietic functions of erythropoietin in mouse models - Vogel, Johannes (Blackwell Science Inc, 2011)
ABSTRACT: As the basic function of erythropoietin (Epo) is stimulation of red blood cell production, systemic overexpression of Epo results in erythrocytosis. The patho-physiological consequences of chronically elevated red blood cell counts have been studied in Epo overexpressing mice. Genetically modified mice, however, have also played an important role in discovering multiple additional functions of Epo besides stimulating erythrocyte production. Non-erythropoietic functions of Epo are widespread and play a role in organogenesis during early embryonic development and in tissue protection in ischaemic diseases. Future work in the field will most likely focus on these additional functions of Epo, which have great clinical potential.